Further evidence of 777 Ma subduction-related continental arc magmatism in Eastern Dom Feliciano Belt, southern Brazil: The Chácara das Pedras Orthogneiss. (July 2016) - Koester, E.; Porcher, C.C.; Pimentel, M.M.; Fernandes, L.A.D.; Vignol-Lelarge, M.L.; Oliveira, L.D.; Ramos, R.C.
Abstract: In this study new SHRIMP U–Pb zircon data for the Chácara das Pedras Gneiss in Porto Alegre, southern Brazil are presented. They represent a small exposure of the crust which was intruded by a large volume of orogenic to anorogenic granitoids at ca. 618-562 m.y. in the Eastern Domain of the Dom Feliciano Belt. The Chácara das Pedras tonalitic orthogneiss has geochemical similarities with subduction-related magmatic rocks of continental arcs. They present high Sr initial ratios (∼0.712), negative ɛNd(t = 777) values (∼−6), TDM varying from 1.8 to 2.0 Ga. The igneous protoliths of these orthogneisses were previously considered to be Paleoproterozoic based on an upper intercept age of discordant zircon analyses. In the present study these orthogneisses were re-sampled and re-analyzed in an attempt to obtain more concordant analytical data. The U–Pb zircon analyses were carried out using the SHRIMP IIe at the Laboratório de Geocronologia de Alta Resolução of the Universidade de São Paulo. The U–Pb concordia age obtained for igneous textural domains of the zircon grains is 777 ± 4 Ma. A few analyses on zircon overgrowths give poorly defined late Cryogenian ages of ca. 650 Ma. Older ages, mostly discordant, were obtained in a few zircon cores, showing an upper intercept age of ca. 1.9 Ga. One sample of the Três Figueiras Granodiorite, which crosscut the orthogneiss in the same outcrop, was also investigated. The zircons of this granodiorite are, however, mostly metamitic, preventing the determination of a reliable age. Some concordant analyses from a few grains define ages ranging in the interval between ca. 603 and 1022 Ma. The youngest (ca. 603 Ma) may represent a maximum age for the granodiorite crystallization. Older ages, with discordance <10%, are of 745, 777, 836 and 1022 Ma. The 777 ± 4 Ma age obtained for the Chácara das Pedras orthogneiss is the first Early Cryogenian magmatic age determined for granitoids in the Porto Alegre region, although records of similar ages (780–800 Ma) are recognized within the Eastern Domain of the Dom Feliciano Belt. Examples are the Piratini Gneisses (Piratini region) and in the Cerro Bori Orthogneisses (Rocha region, Uruguay). All these units show subduction-related continental arc affinities. The identification of a magmatic event of ca. 780–800 Ma in the Porto Alegre region implies that: (i) the collisional magmatism (650 Ma) is ca. 130 Ma younger than the subduction-related magmatism; (ii) the younger orogenic (arc related to post-collisional) and anorogenic granitoids (<618 Ma) of Eastern Domain were emplaced in a hot/weak lithosphere due to the presence of an earlier ca. 780–800 Ma magmatic arc rocks; (iii) the tectonic evolution of this region in West Gondwana suggests a more complex geotectonic scenario than those put forward by previous models involving the amalgamation of the Río de La Plata and Kalahari cratons.